Transcatheter Arterial Chemoembolization Combined with Hepatic Arterial Infusion Chemotherapy Versus Transcatheter Arterial Chemoembolization for Unresectable Hepatocellular Carcinoma: A Systematic Review and Meta-analysis - Feng, Guoying; Feng, Yi; Yao, Shu; Huang, Xun; Peng, Zuxiang; Tang, Yongliang; Tang, Wen; Li, Zhengyan; Wang, Hanchen; Liu, Hongming (Turkish Journal of Gastroenterology, 2024)
Background/Aims: In this study, we evaluated the efficacy and safety of transcatheter arterial chemoembolization (TACE) combined with hepatic arterial infusion chemotherapy (HAIC) compared to TACE monotherapy for the treatment of unresectable hepatocellular carcinoma (HCC). Materials and Methods: Relevant studies were systematically searched in PubMed, Embase, Web of Science, and Cochrane Library databases until September 1, 2023. Our analysis included 7 cohort studies encompassing a total of 630 patients. Results: The results demonstrated that the TACE plus HAIC group exhibited significantly improved prognosis compared to the TACE alone group, as evidenced by superior rates of complete response, partial response, progressive disease, objective response rate, and disease control rate. Moreover, the TACE group displayed a lower risk of platelet reduction and vomiting when compared to the TACE plus HAIC group. None of the 7 studies reported any intervention-related mortality. Conclusion: In conclusion, the combination of TACE and HAIC may be recommended as a viable option for patients with unresectable HCC, given its evident enhancements in survival and tumor response rates without significant differences in adverse events when compared to TACE monotherapy. Nevertheless, additional randomized controlled trials and studies involving Western cohorts are warranted to further validate these findings. Cite this article as: Feng G, Feng Y, Yao S, et al. Transcatheter arterial chemoembolization combined with hepatic arterial infusion chemotherapy versus transcatheter arterial chemoembolization for unresectable hepatocellular carcinoma: A systematic review and meta-analysis. Turk J Gastroenterol. 2024;35(4):266-279.